2021
DOI: 10.3390/toxins13100716
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Occurrence of Cyanotoxins in Lake Karaoun (Lebanon) by Mass Spectrometry, Bioassays and Molecular Methods

Abstract: Lake Karaoun is the largest artificial lake in Lebanon and serves multiple purposes. Recently, intensive cyanobacterial blooms have been reported in the lake, raising safety and aesthetic concerns related to the presence of cyanotoxins and cyanobacterial taste and odor (T&O) compounds, respectively. Here, we communicate for the first time results from a recent investigation by LC-MS/MS covering multiple cyanotoxins (microcystins (MCs), anatoxin-a, cylindrospermopsin, nodularin) in water and fish collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Methylene chloride had the highest content. Methylene chloride has a sweet taste and chloroform-like odor (Wang et al, 2022), is prevalent in water, and is toxic and a hazardous compound (Chen et al, 2013;Hammoud et al, 2021). Hendra et al (2021) extracted dichloromethane from dragon fruit peel and showed that dichloromethane has high antiplasmodial activity.…”
Section: Volatile Substances In Sv Crayfish Meat During Refrigerationmentioning
confidence: 99%
“…Methylene chloride had the highest content. Methylene chloride has a sweet taste and chloroform-like odor (Wang et al, 2022), is prevalent in water, and is toxic and a hazardous compound (Chen et al, 2013;Hammoud et al, 2021). Hendra et al (2021) extracted dichloromethane from dragon fruit peel and showed that dichloromethane has high antiplasmodial activity.…”
Section: Volatile Substances In Sv Crayfish Meat During Refrigerationmentioning
confidence: 99%